El cine documental en Colombia durante la era del sobreprecio, 1972-1978 (2013)
ABSTRACT:This paper introduces a sight of documentary films produced in the country during the period of the “Extra-price’s Law”. The study is focused on the filmmakers and the characteristics of the films produced between 1972 and 1978, based on previous research and production reports from various film catalogs. The article identifies the filmmakers of the period and documentary film’s features such as format, color and length for the films produced in that period, to show trends in the topics, time and the places covered by the tape. Research that helps restore the country’s audiovisual memory.